Instruments, Methods, and Missions for Astrobiology X 2007
DOI: 10.1117/12.734741
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a moderately halo-acidophilic bacterium isolated from Lake Brown, western Australia

Abstract: Compared to prevalent alkaline to neutral hypersaline environments, acidic hypersaline environments have been scarcely studied. However, they hold interest to many researchers in that these environments have similar geological and geochemical characteristics as those found in lithified strata on Mars. Fieldwork indicated that Lake Brown, located in Western Australia, possessed pH values of 3.1-4.5 and salinity between 13.0-23.0%. Water column, groundwater, and sediment samples were collected from the lake duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Benison and Bowen (2006) and Benison et al (2007a, b) suggest that these sediments are close analogues to the depositional and diagenetic facies of the Burns Formation studied by the Mars Exploration Rover Opportunity on Mars . Mormile et al (2003Mormile et al ( , 2007, Benison and Laclair (2003) and Benison et al (2007a, b) investigated the biota in these lakes and their preservation potential as analogues for possible life on Mars. They were particularly interested in how such biota might be recognised by future explorers.…”
Section: Western Australian Acid Lake Systemsmentioning
confidence: 98%
“…Benison and Bowen (2006) and Benison et al (2007a, b) suggest that these sediments are close analogues to the depositional and diagenetic facies of the Burns Formation studied by the Mars Exploration Rover Opportunity on Mars . Mormile et al (2003Mormile et al ( , 2007, Benison and Laclair (2003) and Benison et al (2007a, b) investigated the biota in these lakes and their preservation potential as analogues for possible life on Mars. They were particularly interested in how such biota might be recognised by future explorers.…”
Section: Western Australian Acid Lake Systemsmentioning
confidence: 98%
“…Salinisphaera species are mesophilic, halotolerant and slightly acidophilic (pH range 5.0-7.5), surviving in a range of moderately acidic and saline conditions as well as high concentrations of metal ions. Species belonging to the Salinisphaera genus have been isolated from a range of environments, including hydrothermal vents, solar salterns, brine from salt wells, seawater and marine fish surfaces (Antunes et al, 2003;Mormile et al, 2007;Crespo-Medina et al, 2009;Bae et al, 2010;Gi et al, 2010;Park et al, 2012;Zhang et al, 2012;Shimane et al, 2013). Critically, these species are able to metabolize both autotrophically and heterotrophically (Antunes et al, 2003;Crespo-Medina et al, 2009;Bae et al, 2010;Antunes et al, 2011a;Park et al, 2012;Zhang et al, 2012;Shimane et al, 2013).…”
Section: Diversity Dynamics Of Lake Magicmentioning
confidence: 99%
“…They are polyextreme ecosystems, exhibiting extremely acidic pH and salinities close to saturation. Such environments are of significant microbial interest as they host organisms that are not only capable of withstanding pH and salinity stress, but also survive in the presence of additional stressors such as high metal concentrations and low nutrients (Mormile et al, 2007;Heidelberg et al, 2013;Johnson et al, 2015;Zaikova et al, 2018). Moreover, they serve as a reservoir of novel microbial functions, such as acidophilic microorganisms that have been used for extracting metal ores from sulphide minerals.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria and archaea have been identified in the acid–saline lakes of Western Australia (Hong et al 2006; Mormile et al 2007), and other manifestations of microbial life, including slimy mats and gas release, are readily visible (Bowen et al 2008). Bowen et al (2008) putatively identified the remains of acidophilic microbial colonies in ‘hairy blobs’ from several lakes.…”
Section: Salinity and Aciditymentioning
confidence: 99%